Absence of mutagenicity of plants used to treat gastrointestinal disorders - Santos, F. V.; Andreo, M. [UNESP]; Nasser, A. L M [UNESP]; Moreira, L. M.; Vilegas, Wagner [UNESP]; Cólus, I. M S; Varanda, Eliana Aparecida [UNESP] (National Library of Serbia, 2013)
The Brazilian Savanna (locally called Cerrado) is an important biome presenting several plants that are used in popular medicine. However, the risks associated with the consumption of derivatives from these plants are generally unknown. Studies with compounds obtained from different species have shown the risks of DNA damage. The present work assessed the in vivo mutagenicity of three plant species used in popular medicine to treat human gastrointestinal disorders (Mouriri pusa, Qualea grandiflora and Qualea multiflora). The micronucleus assay was performed in peripheral blood of mice submitted to acute treatments. Results showed that no assessed extracts were mutagenic in vivo. In fact, the absence of mutagenicity in the present study indicates that the extracts do not contain compounds capable of inducing DNA breaks or chromosomal loss. However, further analysis should be performed in others systems to guarantee their safety, mainly to human chronic use.
Keywords: Brazilian savanna; DNA damage; Medicinal plants; Micronucleus assay; Mutagenicity